Pengetahuan dan Sikap Siswa SDN Ranah Singkuang dan SDN Pekanbaru dalam Memilih Pangan Jajanan - Sri Mulyani; Fitria Fitria (LPPM Hang Tuah Pekanbaru, 2023)
Background: Snack Food have an important role in fulfilling the energy and nutritional intake of school-age children, namely snack food that is safe, quality, and nutritious which will greatly determine the competitiveness of the golden generation of Indonesia. Objective: to analyze the description of the knowledge and attitudes of students at SDN Ranah Singkuang Kampar and SDN Pekanbaru in choosing snack food. Methods: This type of research is a descriptive study with a cross-sectional design. The study was conducted from January – September 2021. The samples in this study were students of SDN Ranah Singkuang Kampar and SDN Pekanbaru, grades 4 and 5, which were taken using a total sampling technique, totaling 240 people. The data was collected using a questionnaire and the data were analyzed univariately. Results: the study showed the level of knowledge of students about the selection of snacks and knowledge of hygiene and packaging of snacks in the